ABA-dependent priming of stomatal immunity by the harpin protein PopW restricts entry of Xanthomonas euvesicatoria in tomato - Xiaosi Zhou; Tian Wei; Yuwei Xue; Jiangfei Hu; Yuqing Lin; Lina Xu; Hongwei Zhao; Hongxia Liu (Plant Science, 2026)

Maize yield responses to bio-organic fertilizer N substitution: Stage-specific associations with soil nitrate status, leaf function, and grain filling - Lintao Liu; Hongxia Cao; Haolei Shi; Guoteng Du; Huadong Zhang; Xiaotao Hu (Field Crops Research, 2026)

Harnessing SNPs and InDels from whole-genome sequencing to enhance genomic prediction in sturgeons - Hailiang Song; Wei Wang; Tian Dong; Xiaoyu Yan; Chenfan Geng; Ai Sun; Song Bai; Hongxia Hu (Aquaculture, 2026)

Development and validation of a 40 K liquid SNP array for the sturgeon - Hailiang Song; Tian Dong; Wei Wang; Xiaoyu Yan; Boyun Jiang; Chenfan Geng; Ai Sun; Song Bai; Hongxia Hu (Aquaculture, 2026)

Effects of structural heterogeneity in soil humic acids from distinct river basins on Tl(III) binding-reduction: Kinetics and mechanisms - Hongye Li; Die Hu; Chengxue Ma; Ruixing Huang; Yuheng Huang; Qiang He; Hongxia Liu; Xiaoliu Huangfu (Journal of Hazardous Materials, 2026)

A domain embedding strategy for acoustic wave scattering by moving obstacles - Xuelong Gu; Hongxia Guo; Wenkai Yu; Guanghui Hu; Qi Wang (Computer Physics Communications, 2026)

MXene-supported nanoscale zero-valent iron for Cu(II)-EDTA decomplexation and copper immobilization: Mechanistic insights and application potential - Yuxuan Zhang; Jun Luo; Hongxia Xu; Yuanyuan Sun; Xueyuan Gu; Xin Hu; Bin Gao (Chemical Engineering Journal, 2026)

Adaptability of Chaetomorpha valida (Ulvophyceae) spores to salinity, nutrients and water flow in aquaculture ponds and its invasive evaluation - Dongyue Li; Ronglian Xing; Rui Li; Xuebin Cao; Shujun Hu; Xiaojing Pan; Hongxia Zhang; Lihong Chen; Zhen Yu (Aquatic Ecology, 2026)

Distribution and influencing factors of soil and groundwater pollution at pharmaceutical sites in China - Ying Hou; Yi Shi; Weiguang Zhao; Yifei Liu; Nuchao Xu; Hongxia Hu; Haoyuan Wang; Meng Yu; Bochao Zhang; Guizhen Hao; Hongguang Zheng; Juejun Yao; et al. (Journal of Environmental Sciences, 2026)

Enantioselective migration, degradation, and metabolism of pyriproxyfen and its metabolites from tea garden to cup - Hongxia Li; Yue Hu; Yating Ning; Qing Zhong; Hezhi Sun; Xinru Wang; Mei Yang; Fengjian Luo; Li Zhou; Bingjun Han; Xinzhong Zhang (Food Chemistry, 2026)

Transcriptional Responses of HPG-Axis Genes and Hepatic vtg to 11-Ketotestosterone in Previtellogenic Sterlet (Acipenser ruthenus) - Wei Wang; Ying Dong; Tian Dong; Linan Gao; Hua Zhu; Xuetong Bi; Hongxia Hu (Fishes, 2026)
11-ketotestosterone (11-KT) has previously been shown to promote previtellogenic ovarian development and vitellogenin-related hepatic responses in sterlet (Acipenser ruthenus), but the endocrine genes involved in this process remain unclear. In this study, previtellogenic female sterlets were implanted with slow-release 11-KT strips at 5 or 25 mg/kg for 30 days, and transcriptional responses of HPG-axis-related genes, including GnRH paralogs, gonadotropins, and gonadotropin receptors, were examined in the brain-pituitary complex, liver, and ovary. In the brain-pituitary complex, 11-KT increased fsh expression in the 25 mg/kg group and upregulated fshr in both treatment groups, whereas gnrh paralogs showed limited responses. In the liver, most GnRH- and gonadotropin-related genes were not significantly altered, suggesting that hepatic expression of upstream reproductive-axis genes was not a major in vivo target of 11-KT feedback. The ovary exhibited the strongest response, with increased gnrh2 and fsh expression and reduced gnrh3, fshr, and lhr expression, especially at the higher dose. To further examine receptor-related regulation of hepatic vtg expression, liver tissue was incubated in vitro with 11-KT alone or in combination with the androgen receptor antagonist flutamide or the estrogen receptor antagonist fulvestrant. Flutamide did not abolish 11-KT-induced vtg expression, whereas high-dose fulvestrant reduced both era and vtg expression relative to 11-KT treatment alone. Overall, 11-KT elicited tissue-specific transcriptional responses in HPG-axis-related genes, particularly involving ovarian gnrh2, fsh, fshr, and lhr. The differential antagonist responses observed in liver explants provide in vitro evidence consistent with the involvement of ER-associated signaling in hepatic vtg expression, but do not establish direct receptor-mediated regulation.

Functional noncoding variants within the TBX1 enhancer contribute to tetralogy of Fallot - Jimiao Gao; Tao Jiang; Yingyi Quan; Xinyue Liu; Min Da; Jiang Jiang; Jun Zhou; Hao Sun; Yan Zhou; Wanting Ma; Zicheng Zhang; Yiwei Cheng; et al. (Science China Life Sciences, 2026)

In-plane horizontally gradient LSCF-GDC cathode enabling increased air utilization for solid oxide fuel cell - Qi He; Linzheng Hu; Haoyu Zhao; Hongxia Qu; Qin Zhong; Tenglong Zhu (Fuel, 2026)

Unveiling latent interaction patterns of heavy metals in soils using Bayesian network structure learning: Study from industrial region in central China - Shan Liu; Yanni Li; Changlin Zhan; Hongxia Liu; Jianlin Guo; Tianpeng Hu; Xuanhua Liu; Yifei Wang (Environmental Pollution, 2026)

Genetic diversity of Haemaphysalis longicornis populations in China and their symbiotic association with Coxiella R1 strain - Weiqing Zheng; Junhua Tian; Hongxia Liu; Haijun Hu; Hongna Chen; Lihua Ma; Yinuo Yan; Jintong Fu; Jinzhi Huang; Yongwei Wen; Siyu Fang; Qianfeng Xia (Experimental and Applied Acarology, 2026)

Optimizing genomic mating in sturgeon by incorporating dominance effects from whole-genome sequencing - Hailiang Song; Tian Dong; Wei Wang; Xiaoyu Yan; Chenfan Geng; Ai Sun; Song Bai; Hongxia Hu (Aquaculture, 2026)

Machine learning–assisted feature selection from whole-genome sequencing data improves trait prediction and reveals candidate genes in sturgeon - Hailiang Song; Huijuan Li; Wei Wang; Tian Dong; Xiaoyu Yan; Song Bai; Hongxia Hu (Aquaculture, 2026)

An explainable machine learning model for accurate estimation of residual phthalate esters in Chinese agricultural soils - Weiwei Wang; Laigang Hu; Jialu Xu; Hongxia Zhu; Shuping Xing; Zhen Song; Yuchen Shen; Daohui Lin; Zhou Shi; Kun Yang (Journal of Hazardous Materials, 2026)

Isolation, Genome Sequencing and Proteomic Analysis of a LiCl-Tolerant Bacillus rugosus E-4 Strain from East Taijinar Salt Lake on the Qinghai-Tibet Plateau - Rong Xu; Sha Du; Zihua Liu; Miaomiao Hu; Jianlan Wu; Hongxia Zhu (Current Microbiology, 2026)

An improved real-time quantitative PCR assay for the differentiation of major Listeria monocytogenes serovars - Jing Wang; Fei Dong; Yuchen Wang; Hui Li; Bin Hu; Jingliang Qin; Yijia Wang; Hongxia Wu; Xi Guo (Food Microbiology, 2026)

Formaldehyde detoxification by the moss Racomitrium japonicum - Tiefeng Chai; Feng Lu; Xin Deng; Ningyuan Fei; Xia Hu; Hongxia Xia; Wanting Li; Ke Chen; Ying Dai; Muhammad Ibrar; Yanbao Lei (Environmental Research, 2026)

A Unified Comparative Evaluation of Genomic Prediction Models Across Four Aquaculture Species - Jinxin Zhang; Xiaofei Yang; Wei Wang; Hongxia Hu; Shaogang Xu; Hailiang Song (Fishes, 2026)
Genomic prediction has been increasingly applied in aquaculture selective breeding; however, systematic evaluations of prediction accuracy across multiple aquaculture species and analytical methods under a unified and comparable framework remain limited. In this study, we conducted a comprehensive comparative assessment of genomic prediction performance across four representative aquaculture species, including Atlantic salmon (Salmo salar), gilthead sea bream (Sparus aurata), common carp (Cyprinus carpio), and rainbow trout (Oncorhynchus mykiss), using ten genomic prediction models including GBLUP, Bayesian and machine learning methods. Prediction accuracy varied widely among species and models, ranging from 0.49 to 0.85, and was strongly associated with trait heritability. High-heritability traits consistently achieved higher prediction accuracies, with rainbow trout and common carp exhibiting the best overall performance (0.75–0.83 and 0.73–0.85, respectively), whereas Atlantic salmon and gilthead sea bream showed lower and more variable accuracies (0.49–0.61 and 0.49–0.66). No single model performed optimally across all species. Machine learning-based approaches achieved the highest prediction accuracy in specific cases but exhibited pronounced species-dependent variability, while GBLUP provided stable and well-calibrated predictions with consistently low bias. Incremental SNP feature selection further improved prediction accuracy by 2.8–4.2% in three species using only 0.54–9.64% of the available markers, whereas no improvement was observed for a low-heritability trait. These results show that genomic prediction performance is highly context-dependent and underscores the importance of jointly considering trait genetic architecture, population characteristics, model choice, and marker selection when optimizing genomic selection strategies in aquaculture breeding programs.

Moisture-resistant Al-based MOF with helical SBUs for efficient CO2 adsorption, separation and desorption - Laigang Hu; Weiwei Wang; Ling Jiang; Jinru Hu; Hongxia Zhu; Mengxue Zhang; Jian Wu; Daohui Lin; Kun Yang (Chemical Engineering Journal, 2026)

Rational design of structurally rigidified ketone-peptide deformylase inhibitors with enhanced membrane permeability for combating gram-negative bacterial infections - Zhonghui Zhang; Jidi Hu; Maoqing Shi; Xiaoxiao Gong; Taoda Shi; Hongxia Li; Yu Qian; Wenhao Hu (Molecular Diversity, 2026)

Genomic selection and genome-wide association study for temperature-induced sex reversal trait in a combined common carp population - Jinxin Zhang; Yulai Wei; Hailiang Song; Yi Rong; Wei Hu; Ji Chen; Hongxia Hu (Aquaculture, 2026)

Environmental Behavior and Migration Accumulation of Thallium in Soil and Plant Systems - Yanying Li; Yisheng Ye; Qiang Zhang; Hongxia Zhu; Mo Xu; Qingning Zhang; Yue Hu (Water, Air, & Soil Pollution, 2026)

Advancing Non‐Contact Fish Phenotyping via Optical Sensing: Toward Precision Aquaculture - Kai Lin; Shiyu Zhang; Wei Wang; Tian Dong; Wen Ding; Chenfan Geng; Yihang Lu; Hongxia Hu (Reviews in Aquaculture, 2026)
Non‐contact fish phenotyping has become an essential strategy for precision aquaculture, enabling accurate, high‐throughput, and non‐invasive trait measurement. In this review, a digital phenotyping framework is summarized, including application‐driven trait definition, multimodal data acquisition (2D, 2.5D, and 3D imaging), and automated phenotypic analysis based on computer vision and deep learning. According to current research paradigms, optical phenotyping applications are systematically categorized into three major domains: morphological, behavioral, and appearance‐based phenotyping. Multimodal optical sensing systems now support high‐throughput morphological, behavioral, and appearance‐based phenotyping, enabling applications ranging from biomass estimation and intelligent feeding control to selective breeding, product quality evaluation, species identification, and disease diagnosis. Despite rapid methodological progress, most existing studies remain confined to laboratory or semi‐controlled environments, and large‐scale implementation in commercial production systems is still limited. Key challenges persist in underwater image degradation, posture‐induced measurement uncertainty, data heterogeneity, model generalizability, computational constraints, and the integration of phenotypic and genomic data for precision breeding. Finally, future development pathways are discussed, including efficient and flexible data acquisition platforms, lightweight and real‐time processing, transfer and few‐shot learning, multimodal data fusion, novel phenotype quantification, and standardized open datasets. Based on a comprehensive analysis of over 100 studies, this review maps the current technological landscape and proposes pathways toward scalable, intelligent phenotyping systems that can improve fish welfare, enhance breeding efficiency, and promote sustainable aquaculture management.

Analysis of the Protective Mechanism of PGC-1α/NRF1/2/TFAM Pathway in Cortical Neuron Injury Induced by Oxidative Stress - Jianhua Li; Wenshi Zhang; Wenqiang Hu; Wei Gao; Jian Wang; Jing Li; Yanxia Wang; Weikai Wang; Hongxia Gao; Bin Yi (Bulletin of Experimental Biology and Medicine, 2025)

Recovery of organic nutrients by Chlorella sorokiniana CMBB276 under various light qualities in aquaculture wastewater - Kairui Zhang; Lu Tan; Hongxia Wang; Hu Jin; Baofeng Chen; Jiayi Xie; Tianze Chang; Quan Xu; Xiaoming Zhu; Céline Rebours; Danni Yuan; Lan Wang (Journal of Environmental Management, 2025)

Cotransport of Thallium(I) and kaolinite colloids in quartz sand media containing sodium humate: Ionic strength, pH and kaolinite colloid concentration - Shuangrui Yang; Zhiheng Li; Chengxue Ma; Yuheng Huang; Hongye Li; Die Hu; Hongxia Liu; Xiaoliu Huangfu (Journal of Environmental Sciences, 2025)

Reservoir evolution and property prediction of the Paleogene Apollonia Formation, Western Desert, Egypt - Yongjie Hu; Hong Zhang; Zixuan Liu; Edgar Cross; Ying Li; Shuyuan Shi; Hongxia Liu; EmadEldin Ramy; Rongtu Ma; Chunfang Cai (Journal of African Earth Sciences, 2025)

Nanocellulose-chitosan nanocomplex stabilized pickering emulsions with extremely low internal phase: Stabilization mechanism and application in yogurt - Hongjie Dai; Yuyuan Luo; Xi Zheng; Xiyue Hu; Hongxia Wang; Liang Ma; Hai Chen; Yuhao Zhang (Food Hydrocolloids, 2025)

Effects of leaching amounts and drip irrigation types on water-salt distribution and seed cotton yield in northern Xinjiang, China - Qingyang Hu; Hongxia Cao; Zijian He; Haolei Shi; Zhiwen Ren; Chen Qi (Field Crops Research, 2025)

Polydopamine-modified coal fly ash composite electrodes for improved electroadsorption of uranium - Jianfeng Zhang; Yifei Jiang; Mu You; Jing Zhao; Shuwen Xue; Hongxia Fang; Yijun Wei; Zhimei Sun; Tao Zeng; Ziqi Wan; Mai Xu; Yunhu Hu (Journal of Water Process Engineering, 2025)

Selective degradation of KOH activated biochar adsorbed 4-chlorophenol with fulvic acid by peroxydisulfate - Min Hu; Laigang Hu; Xiaozeng Miao; Limin Duan; Ling Jiang; Hongxia Zhu; Wenhao Wu; Daohui Lin; Kun Yang (Journal of Environmental Chemical Engineering, 2025)

Fabrication and characterization of non-diary whipped creams: Influence of oleogel - Hongjie Dai; Yingjie Liu; Xi Zheng; Xiyue Hu; Liang Ma; Hongxia Wang; Hai Chen; Yuhao Zhang (Food Chemistry, 2025)

Salt leaching with alternate surface and subsurface drip irrigation enhance cotton yield, water use efficiency, desalination rate, desalination efficiency and economic benefit - Zijian He; Hongxia Cao; Qingyang Hu; Chen Qi; Zhijun Li (Field Crops Research, 2025)

A streamlined cloning and toxicity evaluation strategy of toxin-antitoxin systems in insect cells - Yunfei Li; Shizhe Hu; Jing Wang; Liping Lv; Xueting Zhao; Hanbing Li; Weihua Ma; Hongxia Hua; Zhihui Zhu (Pesticide Biochemistry and Physiology, 2025)

Mn oxide-modified biochars with high adsorption capacity for Pb(II) in wastewater: Preparation and adsorption mechanisms - Jiabo Wang; Hongxia Zhu; Yue Hu; Laigang Hu; Zeming Wei; Yan Ying Li; Xinglu Hu (Environmental Research, 2025)

Microbial degradation of DOC released by the mixed culture of Crassostrea gigas and Undaria pinnatifida - Tian Hu; Jie Su; Kuishuang Shao; Shanshan Dong; Yuyang Xie; Yawen Wei; Hongxia Ming; Tingting Shi; Ge Guo; Jingfeng Fan (Regional Studies in Marine Science, 2024)

Environmental applications and toxicity of ionic liquids - Xiuyan Wang; Xin Hu; Dunhan Zhang; Yuxuan Zhang; Hongxia Xu; Yuanyuan Sun; Xueyuan Gu; Jun Luo; Bin Gao (Journal of Environmental Chemical Engineering, 2024)

Carbon dots-based stimuli-responsive hydrogel for in-situ detection of thiram on fruits and vegetables - Hongxia Li; Yanan Hu; Zhen Lin; Xu Yan; Chunyan Sun; Dong Yao (Food Chemistry, 2024)

Heavy metal contamination assessment and source attribution in the Vicinity of an iron slag pile in Hechi, China: Integrating multi-medium analysis - Hongxia Hu; Hongguang Zheng; Fengping Liu; Zhenyu Ding; Zhongshan Wang; Yanghao Peng; Dan Zhang; Yankun Zhang; Yinan Zheng; Aizhong Ding (Environmental Research, 2024)

Decadal trends of black carbon and heavy metal accumulation in a lake sediment core from central China: A historical perspective - Changlin Zhan; Dejun Wan; Yongming Han; Jiaquan Zhang; Shan Liu; Hongxia Liu; Tianpeng Hu; Wensheng Xiao; Junji Cao; Dong Li (CATENA, 2024)

Photoresponse of Ti3C2Tx MXene promotes its adsorptive-reductive removal of Cr(VI) from water - Yuxuan Zhang; Jun Luo; Xiuyan Wang; Dunhan Zhang; Hongxia Xu; Yuanyuan Sun; Xueyuan Gu; Xin Hu; Bin Gao; Hongqiang Ren (Journal of Environmental Management, 2024)

Reclaiming selenium from water using aluminum-modified biochar: Adsorption behaviors, mechanisms, and effects on growth of wheat seedlings - Xiuyan Wang; Tianxiao Li; Xin Hu; Yuxuan Zhang; Dunhan Zhang; Hanshuo Zhang; Hongxia Xu; Yuanyuan Sun; Xueyuan Gu; Jun Luo; Bin Gao (Environmental Pollution, 2024)

Green synthesis of a superhydrophobic porous organic polymer for the removal of volatile organic compounds at high humidity - Hongxia Zhu; Li Gong; Ling Jiang; Xianyu Liu; Laigang Hu; Wenhao Wu; Daohui Lin; Kun Yang (Science of The Total Environment, 2024)

Exploration of formation and in vitro release mechanism of supramolecular self-assembled Licochalcone A eutectogel for food application - Yi Hu; Dan Zhai; Peiyi Liang; Zeying Zheng; Zhuxian Wang; CuiPing Jiang; Yinglin Guo; Hongkai Chen; Chunyan Shen; Yufan Wu; Yankui Yi; Hongxia Zhu; et al. (Food Chemistry, 2024)

Mechanochromic strain sensor by magnetoplasmonic amorphous photonic arrays - Huu-Quang Nguyen; Jeonghyo Kim; Sangjin Oh; My-Chi Nguyen; Dajeong Hwang; Hyojin Kang; Xiaojun Hu; Hongxia Chen; Van Tan Tran; Jaebeom Lee (Chemical Engineering Journal, 2024)

Sources and factors influencing lacustrine carbon burial over the last century: case study of Yinjia Lake, central China - Changlin Zhan; Dejun Wan; Yongming Han; Shan Liu; Jiaquan Zhang; Hongxia Liu; Tianpeng Hu; Wensheng Xiao; Junji Cao (Journal of Paleolimnology, 2024)

Assessing bioavailability risks of heavy metals in polymetallic mining regions: a comprehensive analysis of soils with varied land uses - Shan Liu; Yanni Li; Changlin Zhan; Hongxia Liu; Jiaquan Zhang; Kuangxin Guo; Tianpeng Hu; Bhagawati Kunwar; Lihu Fang; Yanan Wang (Environmental Monitoring and Assessment, 2024)

Retraction Note: Green economic revival acquisition: evaluating impact of digital finance and natural resource development - HongXia Sun; DingHe Hu; Xu Zhang (Environmental Science and Pollution Research, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Regulation of three novel pepper thiothiazolidinones on the fecundity of Spodoptera frugiperda - Bin Tang; Ye Han; Qixuan Mao; Haoyu Fu; Yujia Luo; Liyuhan Hua; Busheng Liu; Gao Hu; Shigui Wang; Nicolas Desneux; Hongxia Duan; Yan Wu (Pesticide Biochemistry and Physiology, 2024)

Systematic study of microzooplankton in mass culture of the green microalga Scenedesmus acuminatus and quantitative assessment of its impact on biomass productivity throughout a year - Yue He; Wei Wei; Mengyun Wang; Hongxia Wang; Jing Jia; Yingchun Gong; Qiang Hu (Bioresource Technology, 2024)

Biocrusts enhance soil nitrogen mineralization and nitrification under experimental warming in a dryland ecosystem - Rui Hu; Hongxia Zhang; Jingyao Sun; Yafeng Zhang; Mingzhu He; Zhishan Zhang (Applied Soil Ecology, 2024)

Cotransport of aged biochar colloids and thallium(I) in water-saturated porous media: Impact of the ionic strength, pH and aging degree - Shuangrui Yang; Yu Cao; Zhiheng Li; Chengxue Ma; Yuheng Huang; Die Hu; Hongxia Liu; Xiaoliu Huangfu (Science of The Total Environment, 2024)

Phthalate and DINCH exposure and ovarian reserve markers among women seeking infertility care - Yangqian Jiang; Yiqun Xu; Shuxin Xiao; Xianxian Zhu; Hong Lv; Lu Zang; Shuifang Lei; Xin Xu; Bo Xu; Xiumei Han; Jin Zhu; Jiangbo Du; et al. (Science of The Total Environment, 2024)

Integration of multiomics analyses reveals unique insights into CD24-mediated immunosuppressive tumor microenvironment of breast cancer - Haihong Hu; Hongxia Zhu; Wendi Zhan; Bo Hao; Ting Yan; Jingdi Zhang; Siyu Wang; Xuefeng Xu; Taolan Zhang (Inflammation Research, 2024)

The implications of lipid mobility, drug-enhancers (surfactants)-skin interaction, and TRPV1 activation on licorice flavonoid permeability - Zhuxian Wang; Hongkai Chen; Tao Liang; Yi Hu; Yaqi Xue; Yufan Wu; Quanfu Zeng; Yixin Zheng; Yinglin Guo; Zeying Zheng; Dan Zhai; Peiyi Liang; et al. (Drug Delivery and Translational Research, 2024)

Eco-utilization of hierarchically structured calcium silicate hydrate for efficient removal of cadmium from synthetic wastewater - Hongxia Fang; Chuncai Zhou; Shihai Xu; Jiaqian Shi; Yunhu Hu; Guijian Liu (Journal of Water Process Engineering, 2024)

The hydrologic nature of swales uncovers remarkable influence of non-topographic factors on catchment-scale soil moisture variation - Yaling Zhang; Yanjia Jiang; Xiangyang Sun; Hongxia Li; Chuan Yuan; Hu Liu; Jinzhao Liu; Carlos R. Mello; Elizabeth W. Boyer; Li Guo (Journal of Hydrology, 2024)

Metal-organic frameworks derived flower-like V2O3/C/N for high‐performance sodium storage - Hongxia Chen; Hanchi Hu; Tao Shen; Haichen Li; Hongming Zhou (Chemical Engineering Journal, 2024)

A novel preparation of microporous nanosilica derived from aluminum-extracted residue of coal fly ash for highly selective CO2 adsorption - Hongxia Fang; Chuncai Zhou; Shihai Xu; Jiaqian Shi; Yunhu Hu; Guijian Liu (Chemical Engineering Journal, 2024)

Whole-genome resequencing of Russian sturgeon (Acipenser gueldenstaedtii) reveals selection signatures associated with caviar color - Hailiang Song; Tian Dong; Wei Wang; Xiaoyu Yan; Boyun Jiang; Shijian Xu; Hongxia Hu (Aquaculture, 2024)

An effective approach for CH4/N2 separation using aluminum-based metal-organic frameworks (MOFs) prepared from coal fly ash - Hongxia Fang; Chuncai Zhou; Shihai Xu; Jiaqian Shi; Yunhu Hu; Guijian Liu; Lei Wu (Fuel, 2024)

Moso bamboo (Phyllostachys edulis) expansion enhances soil pH and alters soil nutrients and microbial communities - Yaoxing Wu; Jiahuan Guo; Zhiying Tang; Tianxiang Wang; Wenting Li; Xiaorong Wang; Hongxia Cui; Xingyi Hu; Lianghua Qi (Science of The Total Environment, 2024)

Long-term response of the microbial community to the degradation of DOC released from Undaria pinnatifida - Yuyang Xie; Jie Su; Kuishuang Shao; Tian Hu; Hongxia Ming; Tingting Shi; Wenjing Wang; Jingfeng Fan (Marine Environmental Research, 2024)

Experimental study on the viscosity of trifluoroiodomethane (R13I1) with polyol ester and polyvinylether lubricating oils - Yubo Chen; Zhao Yang; Yong Zhang; Hongxia He; Yansong Hu (International Journal of Refrigeration, 2024)

Straw management in paddy fields can reduce greenhouse gas emissions: A global meta-analysis - Zijian He; Hongxia Cao; Chen Qi; Qingyang Hu; Jiaping Liang; Zhijun Li (Field Crops Research, 2024)

Dietary condensed tannin exhibits stronger growth-inhibiting effect on Chinese sea bass than hydrolysable tannin - Jianqiang Qiu; Bing Chen; Wen Huang; Hongxia Zhao; Junru Hu; Jiun-Yan Loh; Kai Peng (Animal Feed Science and Technology, 2024)

Selenium Protects Yellow Catfish (Tachysurus fulvidraco) from Low-Temperature Damage via the Perspective Analysis of Metabolomics and Intestinal Microbes - Junru Hu; Lei Wang; Guoxia Wang; Hongxia Zhao; Huijie Lu; Kai Peng; Wen Huang; Zhenxing Liu; Ding Liu; Yuping Sun (Fishes, 2024)
The effects of selenium supplementation in Tachysurus fulvidraco (T. fulvidraco) on low-temperature stress are not known. In this study, 280 healthy T. fulvidraco were divided into two groups, the G0 group (a control group) and the T0 group (a selenium treatment group on a 0.22 mg/kg diet), for a 6-week feeding time. Then, low-temperature stress (water temperature dropped from 26 to 13 °C, with a rate of 1 °C/h) was administered after that. The feeding results showed that selenium increased the percent weight gain (PWG), specific growth rate (SGR), and survival rate (SR) of T. fulvidraco and decreased the feed conversion rate (FCR), but these differences were not significant (p > 0.05). Under low temperatures, selenium still has no significant effects on antioxidant indexes such as glutathione peroxidase (GSH-Px) activity, superoxide dismutase (SOD) activity, and malondialdehyde (MDA) content in serum (p > 0.05). However, metabolomic analysis revealed that selenium caused changes in lipids and lipid-like molles, organic acids and their derivatives, and fatty acyls. Choline, linoleic acid, and glycerophospholipid metabolism pathways; d-arginine and d-ornithine metabolism; valine, leucine, and isoleucine degradation; and biosynthesis pathways, as well as pyrimidine metabolism pathways, were activated to produce these metabolites to combat against this stress. In addition, selenium increased the diversity of intestinal microbes in T. fulvidraco and decreased the relative abundance of Plesiomonas. However, the combined analysis showed the intestinal microbe changes did not affect metabolite production. In summary, selenium activated lipid, carbohydrate, and amino acid metabolism for energy substance provision, reduced the oxidation and production of other harmful substances, and increased the intestinal microbe diversity of T. fulvidraco to improve resistance to low-temperature stress.

Insight into the long-term nonoxidative immobilization of thallium on birnessite - Wanpeng Chen; Yu Liu; Yuheng Huang; Die Hu; Hongxia Liu; Xiaoliu Huangfu (Journal of Cleaner Production, 2024)

Developing amino acid-citric acid-based deep eutectic solvent for food applications: Preparation, characterization, antibacterial activity, biosafety, and formation mechanism exploration - Yi Hu; Peiyi Liang; Zhuxian Wang; Hongxia Zhu; Qiang Liu (Sustainable Chemistry and Pharmacy, 2023)

Mechanistic insights into the improving effects of germination on physicochemical properties and antioxidant activity of protein isolate derived from black and white sesame - Shuai Hu; Hongxia Gao; Linghua Ouyang; Xin Li; Shuilan Zhu; Yong Wu; Linfeng Yuan; Jinying Zhou (Food Chemistry, 2023)

High-efficiency extraction of aluminum and lithium from coal fly ash using a novel sodium pyrosulfate mechanochemical activation - Sodium persulfate pressure leaching technology - Hongxia Fang; Chuncai Zhou; Shihai Xu; Jiaqian Shi; Yunhu Hu; Guijian Liu (Journal of Cleaner Production, 2023)

RETRACTED ARTICLE: Green economic revival acquisition: evaluating impact of digital finance and natural resource development - HongXia Sun; DingHe Hu; Xu Zhang (Environmental Science and Pollution Research, 2023)

Association between PM2.5 exposure and the outcomes of ART treatment: A prospective birth cohort study - Yifan Wang; Yun Qiu; Bo Huang; Jiangbo Du; Liya Liu; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; et al. (Science of The Total Environment, 2023)

Association between prenatal exposure to trace elements mixture and visual acuity in infants: A prospective birth cohort study - Zijin Wang; Yuanyan Dou; Wenhui Guo; Yuan Lin; Yangqian Jiang; Tao Jiang; Rui Qin; Hong Lv; Qun Lu; Guangfu Jin; Hongxia Ma; Zhibin Hu; et al. (Chemosphere, 2023)

Delamination of multilayer Ti3C2T MXene alters its adsorpiton and reduction of heavy metals in water - Yuxuan Zhang; Jun Luo; Biao Feng; Hongxia Xu; Yuanyuan Sun; Xueyuan Gu; Xin Hu; Mu Naushad; Bin Gao; Hongqiang Ren (Environmental Pollution, 2023)

Regulation of antioxidant defense in response to heat stress in Siberian sturgeon (Acipenser baerii) - Wei Wang; Linan Gao; Wenjie Liu; Zhaohui Tian; Xiaowen Wang; Hongxia Hu (Aquaculture, 2023)

Exploring the molecular mechanisms of isoliquiritin extraction using choline chloride-citric acid deep eutectic solvents - Yi Hu; Zhuxian Wang; Peiyi Liang; Hongxia Zhu; Qiang Liu (Sustainable Chemistry and Pharmacy, 2023)

Genipin-mediated subunit-subunit crosslinking of ferritin nanocages: Structure, properties, and its application for food bioactive compound sealing - Hai Chen; Xiaoyi Tan; Mengji Hu; Jiang Xie; Xueer Han; Yong Yu; Hankun Zhu; Hongxia Wang; Yuhao Zhang (Food Chemistry, 2023)

Insights into biodegradation behaviors of methanolic wastewater in up-flow anaerobic sludge bed (UASB) reactor coupled with in-situ bioelectrocatalysis - Yijing Gao; Teng Cai; Jian Yin; Huan Li; Xinyu Liu; Xueqin Lu; Hongxia Tang; Weijie Hu; Guangyin Zhen (Bioresource Technology, 2023)

Ensemble learning system to identify nutritional risk and malnutrition in cancer patients without weight loss information - Liangyu Yin; Jie Liu; Ming Liu; Jin Zheng; Aiguo Xu; Quanjun Lyu; Yongdong Feng; Zengqing Guo; Hu Ma; Jipeng Li; Zhikang Chen; Hui Wang; et al. (Science China Life Sciences, 2023)

Occurrence and exposure risk assessment of organochlorine pesticides in two waterbird species from Honghu Lake Wetland, Central China - Ying Hu; Hongxia Liu; Xinli Xing; Jingjing Lian; Feixiang Liu (Environmental Geochemistry and Health, 2023)

Predictive Control of a Heaving Compensation System Based on Machine Learning Prediction Algorithm - Lifen Hu; Ming Zhang; Zhi-Ming Yuan; Hongxia Zheng; Wenbin Lv (Journal of Marine Science and Engineering, 2023)
Floating structures have become a major part of offshore structure communities as offshore engineering moves from shallow waters to deeper ones. Floating installation ships or platforms are widely used in these engineering operations. Unexpected wave-induced motions affect floating structures, especially in harsh sea conditions. Horizontal motions on the sea surface can be offset by a dynamic positioning system, and heave motions can be controlled by a heave compensation system. Active heave compensation (AHC) systems are applied to control vertical heave motions and improve safety and efficiency. Predictive control based on machine learning prediction algorithms further improves the performance of active heave compensation control systems. This study proposes a predictive control strategy for an active heave compensation system with a machine learning prediction algorithm to minimise the heave motion of crane payload. A predictive active compensation model is presented to verify the proposed predictive control strategy, and proportion–integration–differentiation control with predictive control is adopted. The reliability of back propagation neural network (BPNN) and long short-term memory recurrent neural network (LSTM RNN) prediction algorithms is proven. The influence of the predictive error on compensation performance is analysed by comparing predictive feedforward cases with actual-data feedforward cases. Predictive feedforward control with regular and irregular wave conditions is discussed, and the possible strategies are examined. After implementing the proposed predictive control strategy based on a machine learning algorithm in an active heave compensation system, the heave motion of the payload is reduced considerably. This investigation is expected to contribute to the motion control strategy of floating structures.

Whole-genome resequencing reveals selection signatures for caviar yield in Russian sturgeon (Acipenser gueldenstaedtii) - Hailiang Song; Boyu Zhu; Tian Dong; Wei Wang; Mou Hu; Xiaoyu Yan; Shijian Xu; Hongxia Hu (Aquaculture, 2023)

Phenylethanoid Glycosides of Cistanche Improve Learning and Memory Disorders in APP/PS1 Mice by Regulating Glial Cell Activation and Inhibiting TLR4/NF-κB Signaling Pathway - Chunhui Wang; Hongxia Ye; Yanjie Zheng; Yanqiang Qi; Mengyu Zhang; Yan Long; Yanli Hu (NeuroMolecular Medicine, 2023)

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Genome and transcriptome of Chinese medaka (Oryzias sinensis) and its uses as a model fish for evaluating estrogenicity of surface water - Yue Wang; Jilong Guo; Xiaojing Jia; Xiaozhe Luo; Ying Zhou; Xingtai Mao; Xiaolin Fan; Hongxia Hu; Hua Zhu; Chengxia Jia; Xuan Guo; Lan Cheng; et al. (Environmental Pollution, 2023)

Genome-wide analysis of growth-regulating factor genes in grape (Vitis vinifera L.): identification, characterization and their responsive expression to osmotic stress - Qiang Hu; Binyu Jiang; Liru Wang; Yanjing Song; Xiaoli Tang; Yanhong Zhao; Xiaobin Fan; Yafeng Gu; Qiuling Zheng; Jieshan Cheng; Hongxia Zhang (Plant Cell Reports, 2023)

Recovery of nutrients from aquaculture wastewater: Effects of light quality on the growth, biochemical composition, and nutrient removal of Chlorella sorokiniana - Yuqing He; Jie Lian; Lan Wang; Lu Tan; Fahad Khan; Yanhua Li; Hongxia Wang; Céline Rebours; Danxiang Han; Qiang Hu (Algal Research, 2023)

Genomic selection and its research progress in aquaculture breeding - Hailiang Song; Tian Dong; Xiaoyu Yan; Wei Wang; Zhaohui Tian; Ai Sun; Ying Dong; Hua Zhu; Hongxia Hu (Reviews in Aquaculture, 2023)
Since its introduction in 2001, genomic selection (GS) has progressed rapidly. As a research and application hot topic, GS has led to a revolution in the field of animal and plant breeding. Thanks to its ability to overcome the shortcomings of traditional breeding methods, GS has garnered increasing attention. Both theoretical and practical breeding studies have revealed the higher accuracy of GS than that of traditional breeding, which can accelerate genetic gain. In recent years, many GS studies have been conducted on aquaculture species, which have shown that GS produces higher prediction accuracy than traditional pedigree‐based method. The present study reviews the principles and processes, preconditions, advantages, analytical methods and factors influencing GS as well as the progress of research in aquaculture into these aspects. Furthermore, future directions of GS in aquaculture are also discussed, which should expand its application to more aquaculture species.

Prevalence, antibiotic and heavy metal resistance of Vibrio spp. isolated from the clam Meretrix meretrix at different ages in Geligang, Liaohe estuary in China - Jie Su; Yingxue Zhang; Tian Hu; Hongxia Ming; Yuyang Xie; Yuan Jin; Tingting Shi; Jingfeng Fan (Frontiers in Marine Science, 2022)
Vibrio as one of the main pathogens of shellfish diseases can cause serious human seafoodborne gastroenteritis and even death. In this study, we analyzed the bacterial communities from the clam, and compared the resistance phenotypes and genotypes of Vibrio spp. from Meretrix meretrix at different growth stages. High-throughput sequencing analysis revealed the predominance of Proteobacteria (50%) in the bacterial community and Vibrio was one of the dominant genera in the clam hepatopancreas in the summer. Vibrio abundance in Meretrix meretrix positively correlated with the water temperature (p<0.05). A total of 73 Vibrio isolates from Meretrix meretrix were classified into 19 species and the dominant strains included V. mediterranei (19%) and V. harveyi (11%), V. algolyticus (10%), and V. parahaemolyticus (8%). The species and abundance of Vibrio spp. were the highest in the 3-year-old of Meretrix meretrix compared with clams of other ages in the summer. Among the 73 isolates, 68 Vibrio strains were resistant to other 15 antibiotics except for sulfamethoxazole-trimethoprim with 57 resistant phenotypes. The most prevalent resistance was toward clindamycin (76%), followed by amikacin (63%), ampicillin (62%), rifampicin (62%), vancomycin (57%), and amoxicillin (50%). The ARI values of Vibrio spp. in different ages ranged from 0.13 to 0.18, and ARI values of 3-year-old (ARI=0.18) clams are higher than that of other ages clam. Approximately 72% of the resistant isolates showed multidrug-resistant phenotypes with maximum resistance to 15 antibiotics. Tolerance to heavy metals including Cd, Zn, and Cu was detected in the majority of antibiotic resistant isolates. In addition to the co-resistance to the same class of antibiotics, resistance to cephalosporin (CFP, CEP, CZ) were significantly correlated with penicillins (AMP, AMC) ( p < 0.01), tetracycline ( p < 0.001), sulfanilamide (SXT) ( p < 0.01) and quinolone (CIP) ( p < 0.01). The heavy metal resistance genes copB and nccA were significantly correlated with the clindamycin resistance phenotype ( p <0.01). This study revealed that the habitat of Meretrix meretrix is in low exposure to antibiotics, and a link between heavy metal resistance genes and antibiotic resistance.

Functional characterization of CD49f+ hepatic stem/progenitor cells in adult mice liver - Ziqi Guo; Shiming Pu; Yun Li; Xiaoxia Wang; Suying Hu; Hongxia Zhao; Cheng Yang; Zuping Zhou (Journal of Molecular Histology, 2022)

Establishment of high-cell-density heterotrophic cultivation of Poterioochromonas malhamensis contributes to achieving biological control of Microcystis - Mingyang Ma; Fuchen Wang; Chaojun Wei; Jianping Chen; Hu Jin; Hongxia Wang; Lirong Song; Qiang Hu; Yingchun Gong (Journal of Applied Phycology, 2022)

Identification of A-to-I RNA editing profiles and their clinical relevance in lung adenocarcinoma - Cheng Wang; Mingtao Huang; Congcong Chen; Yuancheng Li; Na Qin; Zijian Ma; Jingyi Fan; Linnan Gong; Hui Zeng; Liu Yang; Xianfeng Xu; Jun Zhou; et al. (Science China Life Sciences, 2022)

Spatial variability and potential controls of soil organic matter in the Eastern Dongting Lake Plain in southern China - Bifeng Hu; Qing Zhou; Changyuan He; Liangxia Duan; Weiyou Li; Gaoling Zhang; Wenjun Ji; Jie Peng; Hongxia Xie (Journal of Soils and Sediments, 2021)

Characterization and complete genome analysis of Bacillus velezensis CB6 revealed ATP synthase subunit α against foodborne pathogens - Haipeng Zhang; Guan-yi Xu; Changsi Mao; Yuxuan Xu; Wenlong Dong; Muhammad Inam; Siyu Pan; Renge Hu; Yiming Wang; Yu Wang; Hongxia Ma; Lingcong Kong (Archives of Microbiology, 2021)

Genome-wide association study identifies QTL for thousand grain weight in winter wheat under normal- and late-sown stressed environments - Xiaobo Wang; Panfeng Guan; Mingming Xin; Yongfa Wang; Xiyong Chen; Aiju Zhao; Manshuang Liu; Hongxia Li; Mingyi Zhang; Lahu Lu; Jinbo Zhang; Zhongfu Ni; et al. (Theoretical and Applied Genetics, 2021)

A special symptom of olfactory dysfunction in coronavirus disease 2019: report of three cases - Chen Chen; Moxian Chen; Cong Cheng; Yun Chi; Zhiliang Hu; Yuan Liu; Shan Huang; Yanling Lv; Chongfeng Liang; Damin Jiao; Yongxiang Yi; Xia Zhang; et al. (Journal of NeuroVirology, 2020)

Clinical characteristics of 24 asymptomatic infections with COVID-19 screened among close contacts in Nanjing, China - Zhiliang Hu; Ci Song; Chuanjun Xu; Guangfu Jin; Yaling Chen; Xin Xu; Hongxia Ma; Wei Chen; Yuan Lin; Yishan Zheng; Jianming Wang; Zhibin Hu; et al. (Science China Life Sciences, 2020)

Identification, Expression, and Interaction Network Analyses of the CDPK Gene Family Reveal Their Involvement in the Development, Ripening, and Abiotic Stress Response in Banana - Meiying Li; Wei Hu; Licheng Ren; Caihong Jia; Juhua Liu; Hongxia Miao; Anping Guo; Biyu Xu; Zhiqiang Jin (Biochemical Genetics, 2020)

Methamphetamine-Induced Cognitive Deficits and Psychiatric Symptoms Are Associated with Serum Markers of Liver Damage - Tingting Zhao; Changping Zhai; Hongmei Song; Yanhai Wu; Chuanhui Ge; Yonglin Zhang; Hongxia Xu; Zhengsuo Chi; Hui Chu; Wei Shi; Xiaodong Cheng; Xin Li; et al. (Neurotoxicity Research, 2020)

Dual-Ligand Modification of PEGylated Liposomes Used for Targeted Doxorubicin Delivery to Enhance Anticancer Efficacy - Cong Li; Chaoyang Lai; Qiujun Qiu; Xiang Luo; Ling Hu; Huangliang Zheng; Yi Lu; Min Liu; Hongxia Zhang; Xinrong Liu; Yihui Deng; Yanzhi Song (AAPS PharmSciTech, 2019)

Novel Self-Assembled Ibrutinib-Phospholipid Complex for Potently Peroral Delivery of Poorly Soluble Drugs with pH-Dependent Solubility - Qiujun Qiu; Mei Lu; Cong Li; Xiang Luo; Xinrong Liu; Ling Hu; Mingqi Liu; Huangliang Zheng; Hongxia Zhang; Min Liu; Chaoyang Lai; Yanzhi Song; et al. (AAPS PharmSciTech, 2018)

Porous nano-cerium oxide wood chip biochar composites for aqueous levofloxacin removal and sorption mechanism insights - Shengze Yi; Yuanyuan Sun; Xin Hu; Hongxia Xu; Bin Gao; Jichun Wu (Environmental Science and Pollution Research, 2018)

Seasonal variation and health risk assessment of atmospheric PM2.5-bound polycyclic aromatic hydrocarbons in a classic agglomeration industrial city, central China - Tianpeng Hu; Jiaquan Zhang; Xinli Xing; Changlin Zhan; Li Zhang; Hongxia Liu; Ting Liu; Jingru Zheng; Ruizhen Yao; Junji Cao (Air Quality, Atmosphere & Health, 2018)

Assessment of organochlorine pesticide contamination in waterbirds from an agricultural region, Central China - Ying Hu; Shihua Qi; Linxi Yuan; Hongxia Liu; Xinli Xing (Environmental Geochemistry and Health, 2018)

Dimorphic expression of sex-related genes in different gonadal development stages of sterlet, Acipenser ruthenus, a primitive fish species - Wei Wang; Hua Zhu; Ying Dong; ZhaoHui Tian; Tian Dong; HongXia Hu; CuiJuan Niu (Fish Physiology and Biochemistry, 2017)

A cis-eQTL genetic variant of the cancer–testis gene CCDC116 is associated with risk of multiple cancers - Na Qin; Cheng Wang; Qun Lu; Tongtong Huang; Meng Zhu; Lihua Wang; Fei Yu; Mingtao Huang; Yue Jiang; Juncheng Dai; Hongxia Ma; Guangfu Jin; et al. (Human Genetics, 2017)

Mechanistic examination of causes for narrow distribution in an endangered shrub: a comparison of its responses to drought stress with a widespread congeneric species - Hongxia Cui; Shuhua Cong; Xianzhong Wang; Haiping Hao; Lei Shi; Huijin Zhang; Zhigang Li; Tianhua Hu; Yongsheng Qin (Trees, 2016)

Expression quantitative trait loci in long non-coding RNA PAX8-AS1 are associated with decreased risk of cervical cancer - Jing Han; Wen Zhou; Meiqun Jia; Juan Wen; Jie Jiang; Jufang Shi; Kai Zhang; Hongxia Ma; Jibin Liu; Jiansong Ren; Min Dai; Zhibin Hu; et al. (Molecular Genetics and Genomics, 2016)

Activation of Toll-like receptor 3 inhibits Marek’s disease virus infection in chicken embryo fibroblast cells - Xuming Hu; Haitao Zou; Aijian Qin; Kun Qian; Hongxia Shao; Jianqiang Ye (Archives of Virology, 2016)

Properties of cloud and precipitation over the Tibetan Plateau - Chenghai Wang; Hongxia Shi; Haolin Hu; Yi Wang; Baike Xi (Advances in Atmospheric Sciences, 2015)

Pharmacokinetics and pharmacodynamics of 3,3′-diindolylmethane (DIM) in regulating gene expression of phase II drug metabolizing enzymes - Tien-Yuan Wu; Ying Huang; Chengyue Zhang; Zheng-Yuan Su; Sarandeep Boyanapalli; Tin Oo Khor; Hu Wang; Hongxia Lin; Murugesan Gounder; Leonid Kagan; Ioannis P. Androulakis; Ah-Ng Tony Kong (Journal of Pharmacokinetics and Pharmacodynamics, 2015)

Genetic variations in DROSHA and DICER and survival of advanced non-small cell lung cancer: a two-stage study in Chinese population - Shuangshuang Wu; Yun Pan; Songyu Cao; Jiali Xu; Yan Liang; Yan Wang; Lei Chen; Yunyan Wei; Chongqi Sun; Weihong Zhao; Zhibin Hu; Hongxia Ma; et al. (Genes & Genomics, 2015)

Identification of polycyclic aromatic hydrocarbons in soils in Taizhou, East China - Guanjiu Hu; Sulan Chen; Wei Shi; Beibei Zhang; Yong Zhang; Juan Huang; Jun Chen; John P. Giesy; Hongxia Yu (Environmental Geochemistry and Health, 2015)

Organochlorine pesticide residues in surface water from Sichuan Basin to Aba Prefecture profile, east of the Tibetan Plateau - Hongxia Liu; Ying Hu; Shihua Qi; Xinli Xing; Yuan Zhang; Dan Yang; Chengkai Qu (Frontiers of Earth Science, 2015)

The MaASR gene as a crucial component in multiple drought stress response pathways in Arabidopsis - Lili Zhang; Wei Hu; Yuan Wang; Renjun Feng; Yindong Zhang; Juhua Liu; Caihong Jia; Hongxia Miao; Jianbin Zhang; Biyu Xu; Zhiqiang Jin (Functional & Integrative Genomics, 2015)

Contamination of organochlorine pesticides in water and sediments from a waterbird-inhabited lake, East Central China - Ying Hu; Linxi Yuan; Shihua Qi; Hongxia Liu; Xinli Xing (Environmental Science and Pollution Research, 2014)

Marek’s disease virus may interfere with T cell immunity by TLR3 signals - Xuming Hu; Wencai Xu; Aijian Qin; Genghua Wu; Kun Qian; Hongxia Shao; Jianqiang Ye (Veterinary Research Communications, 2014)

Ganetespib blocks HIF-1 activity and inhibits tumor growth, vascularization, stem cell maintenance, invasion, and metastasis in orthotopic mouse models of triple-negative breast cancer - Lisha Xiang; Daniele M. Gilkes; Pallavi Chaturvedi; Weibo Luo; Hongxia Hu; Naoharu Takano; Houjie Liang; Gregg L. Semenza (Journal of Molecular Medicine, 2014)

Expression kinetics of chicken β2-microglobulin and Class I MHC in vitro and in vivo during Marek’s disease viral infections - Chuan Yu; Qiu Liu; Aijian Qin; Xuming Hu; Wencai Xu; Kun Qian; Hongxia Shao; Wenjie Jin (Veterinary Research Communications, 2013)

Soil concentrations and soil-air exchange of organochlorine pesticides along the Aba profile, east of the Tibetan Plateau, western China - Hongxia Liu; Shihua Qi; Dan Yang; Ying Hu; Feng Li; Jia Liu; Xinli Xing (Frontiers of Earth Science, 2013)

Transcriptional profile of Marek’s disease virus genes in chicken thymus during different phases of MDV infection - Xuming Hu; Aijian Qin; Ji Miao; Wencai Xu; Chuan Yu; Kun Qian; Hongxia Shao (Archives of Virology, 2013)

Genetic variants at 4q21, 4q23 and 12q24 are associated with esophageal squamous cell carcinoma risk in a Chinese population - Yong Gao; Yisha He; Jing Xu; Lin Xu; Jiangbo Du; Chen Zhu; Haiyong Gu; Hongxia Ma; Zhibin Hu; Guangfu Jin; Xiaofei Chen; Hongbing Shen (Human Genetics, 2013)

Identification of differentially expressed genes in pistils from self-incompatible Citrus reticulata by suppression subtractive hybridization - Hongxia Miao; Yonghua Qin; Jaime A. Teixeira da Silva; Zixing Ye; Guibing Hu (Molecular Biology Reports, 2013)

Disruption of InlC2 enhances the internalization of Listeria monocytogenes by epithelial cells - Jianjun Jiang; Jianshun Chen; Changyong Cheng; Hongxia Hu; Fan Bai; Ning Chen; Genqiang Yan; Weihuan Fang (World Journal of Microbiology and Biotechnology, 2011)

Genetic characterization of E2 gene of classical swine fever virus by restriction fragment length polymorphism and phylogenetic analysis - Ning Chen; Dejiang Li; Xuemei Yuan; Xiaoliang Li; Hongxia Hu; Binglin Zhu; Xiaoyuan Wan; Weihuan Fang (Virus Genes, 2010)

Endocrine-disrupting equivalents in industrial effluents discharged into Yangtze River - Wei Shi; Xiaoyi Wang; Wei Hu; Hong Sun; Ouxi Shen; Hongling Liu; Xinru Wang; John P. Giesy; Shupei Cheng; Hongxia Yu (Ecotoxicology, 2009)

Porcine reproductive and respiratory syndrome viruses predominant in southeastern China from 2004 to 2007 were from a common source and underwent further divergence - Hongxia Hu; Xiaoliang Li; Zhanfeng Zhang; Jiangbing Shuai; Ning Chen; Guangqing Liu; Weihuan Fang (Archives of Virology, 2009)